Carbonate radical ion as a key driver of rapid atmospheric sulfate formation - Yangyang Liu; Xiao Li; Qiuyue Ge; Xiaozhong Fang; Tao Wang; Wenbo You; Wei Wang; Lifang Xie; Kejian Li; Kedong Gong; Le Yang; Runbo Wang; et al. (npj Climate and Atmospheric Science)
Abstract Carbonate radical anion ( $${{\rm{CO}}}_{{3}^{.-}}$$ CO 3 . − ) is generally considered as a marginal intermediate that rarely regulates atmospheric-relevant reactions of significance. Unexpectedly, in this work, employing a suit of the in-field measurements, lab-based validations, improved kinetic numerical calculations, and chemical transport modeling, we demonstrate that $${{\rm{CO}}}_{{3}^{.-}}$$ CO 3 . − gives a significantly overlooked contribution (~54.4%) to overall secondary sulfate formation during dust storm-relevant episodes and ~236.3% increase of SO2 uptake over mineral dust pathway during haze-relevant periods. GEOS-Chem modeling results further emphasize the important position of this radical ion in dust-driven SO2 oxidation chemistry. Our finding leaves this active intermediate no longer a marginal oxidant currently prevailing in the framework of the atmospheric science community. More importantly, after considering this rapid dust-driven sulfate formation channel mediated by carbonate radicals during pollution episodes, this study provides a clear indication that high priority should be given to reducing alkaline soil dust emissions to achieve benefits for air quality.